Pengaruh Pelatihan dan Pengembangan Karir Pegawai terhadap Motivasi Kerja Pegawai di Era Revolusi Industri 4.0 pada Dinas Perhubungan Provinsi Sumatera Utara - Paradiba, Ananda; Pane, Sri Gustina; Sonata, Ilham (JRMB (Jurnal Riset Manajemen & Bisnis), 2023)
This study aims to determine how much influence the training and career development of employees carried out at the Transportation Agency has on employee work motivation. This research method is Quantitative and the technique used in sampling is a saturated sample technique where the entire population is used as a sample with a total of 65 respondents. The data source uses primary data, namely questionnaires (questionnaires), and secondary data obtained from interviews and literature studies. The data analysis technique used is multiple linear regression with the formula Y = a + b1 + X1 + b2 X2 + Ɛ and to determine how much influence employee training and career development have on employee work motivation using the t test and f test comparison techniques.The results of the validity and reliability tests of the questionnaire, each statement item is declared valid and reliable where if Rcalculating Rtabel with the value of all items above the value of 0.2441 and the regression equation Y = 12.239 + 0.096X1 + 0.319X2 + Ɛ is obtained, meaning that every increase of one unit will cause an increase in employee work motivation by 0.096 and 3.19. Knowing whether or not the hypothesis in this study is accepted, the t test technique is used and f count. The t value of training is 2.069 and the t value of employee career development is 2.766 and t table is 1.669 and obtained f count 3.921, while f table is 3.19 and the significance level (0.025 0.05) shows that training (X1) and employee career development (X2) together have a positive and significant influence on employee work motivation (Y)